A study on the perceived sources of stress among graduating dental students class '82 U.P.C.D. - Polintan, Eileen O.
A survey on graduating dental students perceptions of stress indicates that their ability to finish requirements on time, their relation with the faculty as well as academic standing are areas that create the most stress. Physical and psychological symptoms such as tension, depression, fear, fatigue, headaches and appetite loss were some of the most significant findings as possible outcomes of these perceived sources of stress.